Analysis of Language Errors at the Syntactic Level in the Final Project (Thesis) of Students of the Indonesian Language Education Study Program FKIP UMSU (Journal of Social And Education Research, 2023)
This study examines the form of language errors at the syntactic level in the final assignment (thesis) of students of the Indonesian Language Education Study Program, FKIP UMSU. This study aims to describe the forms of language errors at the syntactic level in terms of phrases, clauses and sentences in the final project (thesis) of students of the Indonesian Language Education Study Program FKIP UMSU 2021. The source of the data in this research is the thesis of students of the Indonesian Language Education Study Program FKIP UMSU 2021. This research method is descriptive method using qualitative data analysis techniques. This research instrument was carried out with documentation guidelines. The results showed that 83 data of writing errors at the syntactic level, including the use of redundant elements and inappropriate prepositions, can be found in the phrase structure. There were 88 errors in sentence construction construction recorded at the syntactic level, namely composing sentences without a subject, sentences without a subject and predicate (stupid sentences), redundant sentences, sentences that No appropriate. subject Which excessive (repeat), And unnecessary use of question words.